Analysis of Effect of Ethics Education and Love of Money Perception of Accounting Students in the Preparation of Financial Statements - Yusuf, Hj Marwah (Journal of Education and Vocational Research, 2015)
This study analyzed the influence of ethics education and love of money on student perceptions of accounting in preparing the financial statements. The study population, the entire accounting student at the State University (PTN) in Makassar. Sampling was purposive sampling method, and is chosen, students who have already taken courses and professional ethics. Methods of data collection in this study, is a questionnaire, after the data is collected and analyzed by SPSS. In conclusion, there is no influence of variables and students’ perceptions of ethics education in the preparation of financial statements. With figures from the calculation of the probability of the correlation between the variables of 0.300 <0, 05.20. No influence of variables Love of Money and perceptions of students in the preparation of financial statements with the number probability 0,201 <0, 05.30. There was no difference between the perception of the preparation of financial statements accounting students who have not taken the ethics education courses and students who have taken courses accounting ethics education. Figures probability variable correlation calculation results of 0.201 <0.05.